2010
DOI: 10.1186/1471-2407-10-116
|View full text |Cite
|
Sign up to set email alerts
|

CD133 expression in chemo-resistant Ewing sarcoma cells

Abstract: BackgroundSome human cancers demonstrate cellular hierarchies in which tumor-initiating cancer stem cells generate progeny cells with reduced tumorigenic potential. This cancer stem cell population is proposed to be a source of therapy-resistant and recurrent disease. Ewing sarcoma family tumors (ESFT) are highly aggressive cancers in which drug-resistant, relapsed disease remains a significant clinical problem. Recently, the cell surface protein CD133 was identified as a putative marker of tumor-initiating ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 34 publications
1
56
1
Order By: Relevance
“…The mechanisms of the PDTresistance of the CD133 high population is unknown and should be further explored; however, recently it was shown that CD133 expression is correlated to both chemo-and radiation therapy resistance [39][40][41]. Interestingly, treating prostate cancer cells with short-term differentiation therapy resulted in enhanced photosensitisation of prostate cancer cells [42].…”
Section: Discussionmentioning
confidence: 95%
“…The mechanisms of the PDTresistance of the CD133 high population is unknown and should be further explored; however, recently it was shown that CD133 expression is correlated to both chemo-and radiation therapy resistance [39][40][41]. Interestingly, treating prostate cancer cells with short-term differentiation therapy resulted in enhanced photosensitisation of prostate cancer cells [42].…”
Section: Discussionmentioning
confidence: 95%
“…There are other reports of Ewing sarcoma of the jaw bone initially misdiagnosed and treated as an odontogenic infection. 4,5 Ewing sarcoma and odontogenic abscess might have some common signs and symptoms including swelling, pain, loss of teeth vitality, increased C-reactive protein, leukocytosis, and elevated temperature. Therefore, in those seemingly odontogenic abscesses that do not respond to antibiotic therapy, particularly in the mandible of a young patient, Ewing sarcoma should be considered, and early incisional biopsy is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that specific surface molecules, including cluster of differentiation (CD)133 and CD44, may be markers for certain CSC populations (8)(9)(10)(11). Several studies have indicated that CSCs may demonstrate the ability of increased resistance to chemotherapy, due to the high expression of specific drug transporters, including multidrug resistance protein 1 and adenosine triphosphate (ATP)-binding cassette (ABC) sub-family G member 2 (ABCG2) (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…CD133 has been used as a marker for hematopoietic stem cells (43) and neuronal stem cells (44). Previously, various studies have demonstrated that CD133 is associated with the initiation and progression of cancer stem and progenitor cells, and may be a valuable CSC marker in a variety of tumors, including epithelial cancers and solid sarcomas (10,11,(45)(46)(47)(48)(49)(50). Therefore, the increased expression of CD44 and CD133 in NMFH-1 spherical colonies may account for the increased survival and metastatic ability of these cells.…”
mentioning
confidence: 99%